PENERAPAN PAJAK PROGRESIF KENDARAAN BERMOTOR DI KOTA BOGOR DIKAITKAN PERATURAN DAERAH PROPINSI JAWA BARAT NOMOR 7 TAHUN 2001 TENTANG PAJAK KENDARAAN BERMOTOR (PKB) - Arie Herdiyan; T.N. Syamsah; Mul yadi (Fakultas Hukum Universitas Djuanda Bogor, 2016)
Bogor city as one of the growing city had a growth rate of motor vehicle very rapidly. For motorcycles only the level of development can reach 1000 units of motorcycles and 500 cars per week. The development of these vehicles certainly can be utilized by the Bogor city government to collect taxes to the owner and / or the ruler of the motor vehicle in order to increase sources of revenue (PAD) Bogor City. Progressive taxation of motor vehicles can also be used to inhibit the purchase of motor vehicles in the city of Bogor. Progressive taxation aims to reduce congestion caused by dense numbers of private motor vehicles. However, because many people do not fully understand the application of progressive tax, causing not a few problems occur when residents will pay motor vehicle tax they have to pay a nominal turns them more due to the number of vehicles registered in the name of the citizens despite the fact that such vehicles is no longer controlled. Identification of problems: 1) How does the implementation of a progressive tax on motor vehicle tax payers in Bogor? and How the impact on motor vehicle tax payer with the implementation of a progressive tax in Bogor? The objectives to be achieved in this thesis are: 1) To determine and analyze on the implementation of a progressive tax on taxpayers motor vehicles in the city of Bogor and 2) To determine and analyze the impact on the taxpayer of a motor vehicle with the application of progressive tax in the city of Bogor. This research was conducted using a normative juridical approach. This type of research is used in legal research is a descriptive study law. Descriptive research is research that is intended to provide data as accurately as possible about the people, the state or other symptoms. Results of the discussion that has been done, it can be concluded the application of progressive tax on taxpayers motor vehicles in the city of Bogor has an important role, in addition to functioning as a source of state revenue also has the function of distribution (equity) revenues. Impact on Taxpayers motor vehicle with the application of progressive tax in the city of Bogor impact of the application of progressive motor vehicle sales tax for automotive companies will hit the automotive sector, especially in terms of sales. As for the impact on society can be experienced personally is the saturation point when the purchasing power of the higher vehicle tax.